Effect of hypothyroidism on libido and reaction time in Black Bengal buck* - Gupta, P S P; Sanwal, P C; Varshney, V P (The Indian Journal of Animal Sciences, 2012)
Hypothyroidism was induced using thiourea in 4, 2-year-old, male Black Bengal goats to study its effect on libido and reaction time. Plasma triiodothyronine (T3), thyroxine (T4) and testosterone (T) levels were determined by radioimmunoassay (RIA). Hypothyroidism was induced in the animals by fourth day of treatment itself and the treatment was extended for further 26 days. Plasma testosterone levels were significantly lower than the pretreatment (normal / control) levels. The libido was decreased and the reaction time was increased (nonsignificantly) during the hypothyroid state.